2015
DOI: 10.1016/j.ejsobi.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Responses of microbial community structure to land-use conversion and fertilization in southern China

Abstract: a b s t r a c tA short-term experiment was carried out in southern China to investigate the effects of land-use conversion from rice paddies to vegetable fields and fertilization on soil microbial community structure by analyzing soil phospholipid fatty acid (PLFA) profiles. A split-plot design with four replicates was adopted, in which land use (paddy and vegetable field) was the first-level treatment and fertilization (conventional fertilization and no fertilization) was nested as the second level. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
5
12
1
Order By: Relevance
“…4). This is consistent with the results presented by Yuan et al (2015). It was noted that a higher fungal/bacterial ratio indicated better sustainability because fungi have a greater growth yield efficiency compared with bacteria, and thus have slow C turnover (Thiet et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…4). This is consistent with the results presented by Yuan et al (2015). It was noted that a higher fungal/bacterial ratio indicated better sustainability because fungi have a greater growth yield efficiency compared with bacteria, and thus have slow C turnover (Thiet et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with our first hypothesis, the recent conversion from paddy fields to drained fields significantly changed the soil properties. These influencing patterns and extents on soil properties were similar for conversed MM and SP, which confirms the role of land use conversion (from paddy fields to drained fields) in altering soil properties (Darilek et al, 2010;Yuan et al, 2015). It was obvious that the soil water content decreased significantly after conversion from RR to MM and SP (Table 1), even though the soil samples were collected at crop harvest after the rice fields had been drying.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…They concluded that the crop rotation provides better soil hydrological conditions, effective rhizodepositions and residual fertility which usually stimulate high proportion of soil microorganisms. Yuan et al (2015) also suggested that the differences in quantity, quality and distribution of papaya residues generally lead to greater concentrations and diversity of organic materials, and thus, to higher soil microbe viability, and accelerated carbon and nutritional cycling compared with pineapple and rice. In tillage systems, the abundance of primary decomposers, such as bacteria and fungi was much greater in NT than in CT, which was instantiated by the higher abundance of bacterivores and fungivores in NT compared with CT ( Fig.…”
Section: Changes Of Soil Nematode and Microbial Communitiesmentioning
confidence: 96%
“…The topsoil (0-10 cm) has an organic carbon content of 9.40 g kg −1 and total N content of 1.00 g kg −1 . The soil pH was 4.99, and the bulk density was 1.30 g cm −3 (Yuan et al 2015).…”
Section: Site Descriptionmentioning
confidence: 99%